Pengaruh Kompetensi Karyawan dan Fasilitas Kerja Terhadap Produktivitas Kerja Karyawan Di Kantor Pusat PT. TRI BANYAN TIRTA - Sulistiani Sulistiani; Yayak Heriyanto; Indra Sumarna Sobari (JAMBIS : Jurnal Administrasi Bisnis, 2023)
The low work productivity of employees will have an impact on the low quality of service to consumers or the public. Based on the author's observations at PT. TRI BANYAN TIRTA, the low work productivity of employees is caused by the lack of supporting facilities in carrying out activities, such as the availability of vehicle facilities, room facilities, filing facilities, software facilities that have not been able to fully support the increasing work activities of employees. This study aims to analyze how much influence Employee Competence and Work Facilities have on Employee Work Productivity at PT. TRI BANYAN TIRTA. The research method in this study used a quantitative approach with data collection techniques through questionnaires and then statistical analysis was carried out using the SPSS version. 24.0. the results of this study concluded that: Employee competence has a significant effect on work productivity with a percentage level of influence of 29.1%. This shows that Employee Competence affects the Work Productivity of PT. Tri Banyan Tirta. Work Facilities have a significant effect on Work Facilities with a percentage level of influence of 29.80%. This shows that Work Facilities affect the Work Productivity of PT. Tri Banyan Tirta. Employee competence and work facilities simultaneously have a significant effect on the level of work productivity of 34.70% while the remaining 65.30% is influenced by other factors not examined in this study.